Filantropi Islam dalam Pertumbuhan Ekonomi Umat melalui Ziswaf - Zainudin, Muhammad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Humans are social beings (Zoon Politicon) who need each other to fulfill their primary and secondary needs. In the Qur'an and Hadith, ta'awun attitude in life is prescribed so that growth continues according to Sunnatullah. The purpose of this research is to provide an understanding of the role of Islamic philanthropy in its contribution to the economic growth of the ummah through an attitude of individual and social generosity aimed at bridging the socio-economic gap in society. Islamic philanthropy also aims to build the economic growth of the ummah in various fields such as education, health, finance and Islamic da'wah through ZISWAF institutions. This research is a library research with qualitative descriptive data analysis. The results of this research show that Islamic philanthropy through ZISWAF is able to overcome the economic disparities of the ummah through the generous hands of individuals and socially. Judging from the data from the National Amil Zakat Agency (BAZNAS), which has succeeded in collecting ZISWAF of Rp. 21.3 trillion in 2022, or an increase of 52.14% compared to 2021 which reached Rp. 14 trillion, this proves that the role of Islamic philanthropy through institutions (BAZNAS) is able to play its role as a driving force for economic growth.